The influence of jet engine noise on hearing of technical staff - Wiesław Konopka; Małgorzata Pawlaczyk-Łuszczyńska; Mariola Śliwińska-Kowalska (Nofer Institute of Occupational Medicine, 2014)
Background: Due to high sound pressure levels (SPLs), noise produced by jet planes may be harmful to hearing of people working in their proximity. The aim of this study was to assess the effects of exposure to jet engine noise on technical staff hearing. Material and Methods: The study comprised 60 men, aged 24-50 years, employed in army as technical staff and exposed to jet engine noise for 6-20 years. The control group were 50 non-noise exposed males, aged 25-51 years. Exposure to noise emitted by jet engines was evaluated. Pure-tone audiometry (PTA) and distortion product otoacoustic emissions (DPOAE) were recorded in both groups. Results: Jet engines emitted broadband noise with spectrum dominated by components in the frequency range 315-6300 Hz (1/3-octave bands). Maximum A-weighted SPL during tests reached values of approx. 120-130 dB. Consequently, engine-servicing personnel (even in the case of a single engine test) was exposed to noise (at A-weighted daily noise exposure level above 95 dB) exceeding permissible levels. Averaged audiometric hearing threshold levels of technical staff were higher (≤ 17 dB HL, p < 0.001) than in the control group. Similarly, the DPOAE amplitude was lower (≤ 17 dB SPL, p < 0.01) in the noise-exposed subjects compared to the non-exposed ones. Significant reduction of DPOAE levels was mainly noted for high frequencies (3-6 kHz). Conclusions: Despite the usage of hearing protection devices, both PTA and DPOAE consistently showed poorer hearing in engine-servicing personnel vs. control group. Med Pr 2014;65(5):583-592